Keratitis due to Chaetomium sp. - Jayaraman Kaliamurthy; Catti Munuswamy Kalavathy; Christadoss Arul Nelson Jesudasan; Philip A. Thomas (Case Reports in Ophthalmological Medicine)
Aim. To describe keratitis due to Chaetomium sp. occurring in a 65-year-old woman who presented with a corneal ulcer with hypopyon of the right eye with a history of trauma by vegetable matter. Method. Multiple scrapings were obtained from the ulcer. A lactophenol cotton blue wet mount and a Gram-stained smear of the scrapings were made. Scrapings were also inoculated onto various culture media. Results. Direct microscopy of corneal scrapings revealed moderate numbers of septate fungal hyphae. Greenish-yellow-coloured fungal colonies with aerial mycelium were observed in culture of the corneal scrapes. On the basis of colony characteristics and conidial structure, the fungal isolate was identified as Chaetomium sp. The patient was treated with topical natamycin (5%) hourly and cyclopentolate 1% drops 3 times a day. After 4 weeks of therapy, the hypopyon had disappeared, the epithelial defect had healed, and the stromal infiltration had almost completely resolved; the visual acuity of the eye improved from hand movements to (1/2)/60. Conclusion. Fungi of the genus Chaetomium, which are rare causes of human disease (systemic mycosis, endocarditis, subcutaneous lesions), may also cause ocular lesions.